Coupling of CE-MS for protein and peptide analysis - Mikšík, Ivan (Wiley-VCH, 2019)
The review is focused on the latest developments in the analysis of proteins and peptides by capillary electrophoresis techniques coupled to mass spectrometry. First, the methodology and instrumentation are overviewed. In this section, recent progress in capillary electrophoresis with mass spectrometry interfaces and capillary electrophoresis with matrix-assisted laser desorption/ionization is mentioned, as well as separation tasks. The second part is devoted to applications-mainly bottom-up and top-down proteomics. It is obvious that capillary electrophoresis with mass spectrometry methods are well suited for peptide and protein analysis (proteomic research) and it is described how these techniques are complementary and not competitive with the often used liquid chromatography with mass spectrometry methods.
Spojení CE-MS pro anaýzu peptidů a bílkovin
Keywords: capillary electrophoresis; mass spectrometry; peptides; proteins; kapilární elektroforéza; hmotnostní spektrometrie; peptidy; bílkoviny